Assessment on awareness of the medical primary care nurses on the existing oral health services in Kuantan, Malaysia, 2012 - Tin, Myo Han; Md Aris, Mohd Aznan; Tuan Ismail, Tuan Sahardi; Thuraiappah, D. M; Tin, Maung Aung; Yusoff, Azizah; Sulong, Robiatu Adawiah (2013)
Background: Oral health is a part of the general health. Evidences of some patients sought the treatment for their oral health problems at medical primary care clinics were found in Anderson et al (1999), Lockhart (2000) and Tin Myo Han et al (2012) study. Thus, role medical primary health care providers are recognizable in educating patients about the importance of good oral hygiene, good eating habits and regular oral health care, and also to guiding patients into oral health services. In accordance with nature of the medical primary care practices, nurses are one of the most suitable staff from medical primary care team for oral health education promotion. Objectives: To assess the awareness of the existing oral health services by the nurses from the 3 selected medical primary care clinics of Kuantan Methods: A cross sectional descriptive and analytical study was carried out by using a pre-tested, semi-structured, self –administered questionnaires to assess the awareness of the existing oral health services and receiving oral health education of 33 nurses from the 3 selected medical primary care clinics; Primary Care Clinic, International Islamic University (Kuantan campus), Klinik Kesihatan( Balok) and a private clinic named “Clinic Ar Razi”, in Kuantan from April to August 2012. The awareness differences among 3 medical primary care clinics on existing oral health services was analysed by x2 test. Results: All 33 nurses from the 3 clinics under study participated. Proportion of the nurse from Klinik Kesihatan( Balok), Clinic Ar Razi and Primary Care Clinic (IIUM) were 52%(17/33) , 33%(11/33) and 15% (5/33) respectively. Most of them were female nurses (73%) and had university level education (64%). Regarding knowledge on existing oral health services, knowing the present of dental clinics (73%), total number of dental clinic (73%), type of dental clinic (74%), opening days and time (52%) and knowing dentists and dental nurses from the dental clinics nearby (51.5%) were noticed. Regarding the services provided in the dental clinics, 21%(7/33) were unsure what services provided at dental clinics; one-third of them mentioned only treatment for dental caries; 12%(4/33) mentioned treatment for dental caries and gingival diseases; and 33%(11/33) mentioned the treatment for common dental treatments such as caries, gingival diseases, denture, oral ulcers, lump in oral cavity and cosmetic dentistry (tooth alignment). Knowledge on accessibility of dental clinic for routine dental health problems, that of the emergency dental problems and consulting with oral health providers anytime were 91%, 54.5% and 79% respectively. Ninety-one percents of them had already received oral health education from oral health talk, media and oral health providers. More awareness of Klinik Kesihatan( Balok) clinic nurses on the dental clinic opening date and time and more positive answer on availability of consulting oral health personal anytime were significantly found. Conclusion: Positive findings of this study highlight the feasibility of the medical primary care nurses as one of key oral health educators to promote the oral health education and provide the available oral health services information among the patients attending at medical primary care clinics.